2022
DOI: 10.1007/s13202-021-01412-x
|View full text |Cite
|
Sign up to set email alerts
|

Movement behavior of residual oil droplets and CO2: insights from molecular dynamics simulations

Abstract: After primary and secondary recovery of tight reservoirs, it becomes increasingly challenging to recover the remaining oil. Therefore, improving the recovery of the remaining oil is of great importance. Herein, molecular dynamics simulation (MD) of residual oil droplet movement behavior under CO2 displacement was conducted in a silica nanopores model. In this research, the movement behavior of CO2 in contact with residual oil droplets under different temperatures was analyzed, and the distribution of molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…The pore-scale CO 2 diffusion in oil has been characterized by MD. Luo et al studied CO 2 diffusion to displace n -nonane in nanometer pores. They found that CO 2 molecules disperse residual n -nonane droplets and replace n -nonane molecules adsorbed on the pore wall (Figure a).…”
Section: Mass Transfer Between Co2 and Oil At The Nanoscalementioning
confidence: 99%
See 1 more Smart Citation
“…The pore-scale CO 2 diffusion in oil has been characterized by MD. Luo et al studied CO 2 diffusion to displace n -nonane in nanometer pores. They found that CO 2 molecules disperse residual n -nonane droplets and replace n -nonane molecules adsorbed on the pore wall (Figure a).…”
Section: Mass Transfer Between Co2 and Oil At The Nanoscalementioning
confidence: 99%
“…(a) CO 2 molecule diffusion to replace n -nonane molecules adsorbed on the silica surface and residual oil droplets. This panel was reprinted with permission from ref . Copyright 2022 Springer Nature.…”
Section: Mass Transfer Between Co2 and Oil At The Nanoscalementioning
confidence: 99%